2016
DOI: 10.1002/zaac.201600346
|View full text |Cite
|
Sign up to set email alerts
|

A Dinuclear Gold(I) Bis(Carbene) Complex Based on a Ditopic Cyclic (Aryl)(Amino)Carbene Framework

Abstract: A dinuclear gold(I) bis(carbene) complex based on a 1,5dihydropyrazolo[3,4-f]indazoline-3,7-diylidene ligand framework is reported. The bridging bis(carbene) ligand is the first example of a ditopic cyclic (aryl)(amino)carbene (CArAC). The ligand precursor 2,6-diethyl-1,5-diphenyl-1,5-dihydropyrazolo[3,4-f]indazole-2,6-diium (2H 2 ) is readily available from the literature-known starting material 1,5-diphenyl-1,5-dihydropyrazolo[3,4-f]indazole (1) and two equivalents of the Meerwein salt [Et 3 O][BF 4 ]. The N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 87 publications
1
4
0
Order By: Relevance
“…Related to these type of Janus di-NHCs, in 2016 the group of Breher's described a benzo-fused di-pyrazolylidene and its coordination to gold (60, in Scheme 19). 47 The authors performed detailed experimental and computational studies (on Rh-based model complexes 61) in order to determine the ability of the ligand to mediate electronic metal-to-metal communication, and concluded that this coupling is a direct function of the number of metal-ligand contacts, in line with the findings published by Albrecht and co-workers for the Janus-bisimidazolylidene 44. 42 Although the benzo-bis-NHCs ligand in 60 and 61 do not establish the coordination to the two metals strictly in a 'directionally-opposed' manner, we consider it a close relative of the Janus-di-NHC family.…”
Section: Janus Di-nhcs With Fused Polycyclic Aromatic Hydrocarbon Spa...supporting
confidence: 65%
“…Related to these type of Janus di-NHCs, in 2016 the group of Breher's described a benzo-fused di-pyrazolylidene and its coordination to gold (60, in Scheme 19). 47 The authors performed detailed experimental and computational studies (on Rh-based model complexes 61) in order to determine the ability of the ligand to mediate electronic metal-to-metal communication, and concluded that this coupling is a direct function of the number of metal-ligand contacts, in line with the findings published by Albrecht and co-workers for the Janus-bisimidazolylidene 44. 42 Although the benzo-bis-NHCs ligand in 60 and 61 do not establish the coordination to the two metals strictly in a 'directionally-opposed' manner, we consider it a close relative of the Janus-di-NHC family.…”
Section: Janus Di-nhcs With Fused Polycyclic Aromatic Hydrocarbon Spa...supporting
confidence: 65%
“…The chemistry of the heavier homologues of N‐heterocyclic carbenes (NHCs) such as silylenes, germylenes, stannylenes and plumbylenes called tetrylenes, has been less intensively explored than that of NHCs . N‐heterocyclic carbenes show bonding similar to that of electron‐rich trialkylphosphanes with strong σ‐donors with negligible π‐accepting ability . More recent studies have shown that NHCs have a significant π‐accepting ability, which, however, is much weaker that its strong σ‐donor ability.…”
Section: Introductionmentioning
confidence: 99%
“…Gold complexes can be prepared by deprotonation of the corresponding aldiminium salts with LiN­(SiMe 3 ) 2 at −78 °C in the presence of (Me 2 S)­AuCl as shown for 50a , whereas the copper analogue is obtained by treatment of the salt precursor with CuOAc . Alternatively, a transmetalation route can be used as exemplified by the preparation of 51 , , or even by reaction with the Nolan NHC gold­(I) hydroxide [IPrAuOH} , as described by Breher et al for the dinuclear complex 52 (Scheme ). Note that complexes based on ditopic NHCs, analogous to 52 have been discussed as building blocks for electronically coupled systems. , …”
Section: Coordination Chemistry Of Cyclic (Alkyl)- and (Aryl)-(amino)...mentioning
confidence: 99%
“…Gold complexes can be prepared by deprotonation of the corresponding aldiminium salts with LiN(SiMe 3 ) 2 at −78 °C in the presence of (Me 2 S)AuCl as shown for 50a, 12 whereas the copper analogue is obtained by treatment of the salt precursor with CuOAc. 106 Alternatively, a transmetalation route can be used as exemplified by the preparation of 51, 13,107−109 or even by reaction with the Nolan NHC gold(I) hydroxide [IPrAuOH} 32,110 as described by Breher et al 111 for the dinuclear complex 52 (Scheme 16). Note that complexes based on ditopic NHCs, analogous to 52 have been discussed as building blocks for electronically coupled systems.…”
Section: Synthesis Of Saturated Abnormal Carbene and Cyclic (Aryl)(am...mentioning
confidence: 99%